PENGARUH KADAR AIR TERHADAP TEGANGAN TEMBUS MINYAK TRANSFORMATOR DISTRIBUSI - Christine Widyastuti; Tasdik Darmana; Oktaria Handayani (Sekolah Tinggi Teknik PLN, 2018)
Abstract Transformer oil is one of the liquid insulating materials that functions as insulation and cooling in the transformer. Some oil insulation materials must have the ability to withstand penetrating stresses, while as a transformer oil cooler must be able to reduce the heat generated, so that with these two capabilities transformer oil is expected to be able to protect the transformer from interference. Examination of breakdown stress using the IEC 60156-1995 method. For evaluation of oil on the power transformer determines the water content. The feasibility of transformer oil uses breakdown voltage and water content testing as a result of feasibility simulations based on international standards to improve reliability in the treatment of power transformers in the industrial world especially for community service. With greater breakdown voltage, it proves that the oil is still suitable for use. Whereas if the oil water content is higher, it proves that the oil is not suitable for use. Transformer oil, according to the PLN (SPLN) test standards 49-1 / 1992, must have a 30kV / 2.5mm breakdown voltage. In the study of sample A and sample B it has a breakdown voltage of 14kVA and 18kVA. With this, sample A and sample B are not suitable for use. Keywords: moisture content, transformer oil, breakdown voltage, SPLN 49-1 / 1992 ABSTRAK Minyak transformator merupakan salah satu bahan isolasi cair yang berfungsi sebagai isolasi dan pendingin pada transformator. Sebagian bahan isolasi minyak harus memiliki kemampuan untuk menahan tegangan tembus, sedangkan sebagai pendingin minyak transformator harus mampu meredam panas yang ditimbulkan, sehingga dengan kedua kemampuan ini maka minyak transformator diharapkan mampu melindungi transformator dari gangguan. Pengujian tegangan tembus menggunakan metode IEC 60156-1995. Untuk evaluasi minyak pada transformator daya menentukan kadar air. Kelayakan minyak transformator menggunakan pengujian tegangan tembus dan kadar air sebagai hasil simulasi kelayakan berdasarkan standar internasional untuk meningkatkan kehandalan dalam perawatan transformator daya dalam dunia industri khususnya terhadap pelayanan masyarakat. Dengan tegangan tembus yang semakin besar membuktikan minyak tersebut masih layak pakai. Sedangkan apabila kadar air minyak tersebut semakin tinggi membuktikan minyak tersebut sudah tidak layak pakai. Minyak transformator, sesuai standar uji PLN (SPLN) 49-1/1992 harus memiliki tegangan tembus 30kV/2,5mm. Dalam penelitian dari sampel A dan sampel B memiliki tegangan tembus sebesar 14kVA dan 18kVA. Dengan ini, sampel A dan sampel B tidak layak pakai. Kata kunci: kadar air, minyak trafo, tegangan tembus, SPLN 49-1/1992